FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KEDISIPLINAN KERJA PEGAWAI BAGIAN UMUM DAN PROTOKOL SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Alexander Sampeliling (KINERJA, 2015)
This study aimed to analyze factors - factors that affect the level of employee discipline, in this study the research object is a common part and the protocol secretariat east Kutai district, the variables of this research is concern leadership, compensation, exemplary leadership, supervisory leadership, rules sure, leadership and courage while the dependent variable is work discipline. The population in this study were employees registered and placed on the public and the protocol in east Kutai district secretariat that the total amounted to 87 people, an analysis tool used is multiple regression, the results of the test results of data analysis showed that of the entire independent variables use, have a positive influence on employee discipline, while for the attention of the leadership becoming more dominant variable of six existing variables by obtaining a value of 0.199 (19.9%) and t value of 2.438. Keywords: Disciplinary, Compensation, Exemplary leadership